Feline Musculoskeletal Pain Index: Responsiveness and Testing of Criterion Validity. (3rd April 2013) - Benito, J.; Hansen, B.; DePuy, V.; Davidson, G.S.; Thomson, A.; Simpson, W.; Roe, S.; Hardie, E.; Lascelles, B.D.X.
<x xml:space="preserve">Abstract</x> Background Progress in establishing if therapies provide relief to cats with degenerative joint disease (DJD)‐associated pain is hampered by a lack of validated owner‐administered assessment methods. Hypothesis That an appropriately developed subjective owner‐completed instrument (Feline Musculoskeletal Pain Index‐FMPI) to assess DJD‐associated impairment would have responsiveness and criterion validity. Animals Twenty‐five client‐owned cats with DJD‐associated pain. Methods FMPI responsiveness (ability to detect the effect of an analgesic treatment) and validity (correlation with an objective measure) were explored through a stratified, randomized, double blinded, placebo‐controlled, crossover 10‐week clinical study. Meloxicam was administered to effect pain relief. A linear mixed model, backward stepwise regression, and Pearson correlations were used to assess responsiveness and criterion validity with the assumption that the NSAID would increase activity. Results Positive responses of cats to placebo (P = .0001) and meloxicam treatment (P = .0004) were detected; however, the instrument did not detect any difference between placebo and meloxicam (linear mixed model), even for the high impairment cases. Percent meloxicam target dose administered, temperament, and total baseline FMPI score were covariates that most affected FMPI scores. Controlling for significant covariates, most positive effects were seen for placebo treatment. Positive treatment effects on activity were detected, but only for the cases designated as most highly impaired. Conclusions and Clinical Importance Neither responsiveness nor criterion validity were detected by the inclusion criteria for cases in this study. The data suggest that further work is indicated to understand factors affecting activity in cats to optimize inclusion criteria.